Inventory and Assessment of Carbon Storage Capacity of Non-Timber Plants in Universiti Tun Husein Onn Malaysia, Main Campus, Batu Pahat, Johor Malaysia - Audu, Yunusa; Linatoc, Alona Cuevas (Journal of Science and Technology, 2017)
Carbon dioxide, an important greenhouse gas performs a fundamental role in Earth's carbon cycle. Its continuous rise has been observed to result to enhanced greenhouse effect which has led to global warming. The increase in CO2 discharge in UTHM (238.8964 ha), owing to more vehicles, and other greenhouse gases from building amenities and close by industries is a concerning issue. Nineteen most common nontimber plants were studied for their capacity to sequester significant amount of CO2. Estimation of carbon storage of non-timber plants was obtained by assessments of standing biomass and their photosynthetic capacity. Results indicate that Sanchezia speciosa has the highest CO2 absorption capacity (15.37µmol m-2 s-1) followed by Hibiscus rosa S. (11.27µmol m-2 s-1), and Ixora coccinea with (9.90µmol m-2 s-1). Baphia nitida has the highest aboveground biomass accumulation (1.0620 kg), followed by Tabernae montana (0.6842 kg), and Cordyline fruticosa (0.1597 kg). Ixora coccinea has the highest biomass accumulation (646.4160 kg), followed by Tabernae montana (220.9966 kg), and Baphia nitida (129.5640 kg) on species abundance. The total biomass captured by the all the species is 1319.2486 kg (1.3192 tons) of carbon. Hence, species of non-timber plants in UTHM have the capacities to absorb a substantial quantity of CO2 from the atmosphere thus contributing to reducing the effects of world-wide warming and climate alteration.